Encyclopedia of Information Science and Technology, Fourth Edition 2018
DOI: 10.4018/978-1-5225-2255-3.ch004
|View full text |Cite
|
Sign up to set email alerts
|

An Extension to the Delone and Mclean Information Systems Success Model and Validation in the Internet Banking Context

Abstract: The modern internet era opened a plethora of opportunities for doing business online. Internet banking (IB) is one such innovation which made greater strides from the humble beginnings in the mid 1990s. It is important for Bank practitioners to know what are the factors contributing to the success of new technology by customers to enable them better placed in the competitive segment. This study proposes an extension to the Delone and Mclean IS Success model to evaluate Information Systems(IS) success in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Several studies have indicated that in a mandatory setting of an IS, irrespective of the quality antecedents, the SQ and IQ would have no or little effect on SU (Iivari, 2005;Jagannathan et al, 2018;Lwoga, 2012;Yakubu & Dasuki, 2018). This study supports this notion, as no significant link was found between SQ and SU, or between IQ and SU.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that in a mandatory setting of an IS, irrespective of the quality antecedents, the SQ and IQ would have no or little effect on SU (Iivari, 2005;Jagannathan et al, 2018;Lwoga, 2012;Yakubu & Dasuki, 2018). This study supports this notion, as no significant link was found between SQ and SU, or between IQ and SU.…”
Section: Discussionmentioning
confidence: 99%
“…The D&M Information System Model is a well-known and influential framework designed to elucidate the various aspects and impacts of information systems (IS) [ 21 ]. The model has been revised and adjusted since it was first put forth by DeLone and McLean [ 22 ].…”
Section: Theoretical Ground and Hypothesis Developmentmentioning
confidence: 99%
“…The updated D&M's ISS model developed by DeLone & McLean (2003) to understand the field of e-commerce, but it applied in different sectors to measure the quality factors of information systems. Many authors have extended this model in e-commerce (Hsu et al (2014)), acceptance of internet banking (Jagannathan et al 2018) by adding new constructs. Whereas, other researchers have validated the model by studying Knowledge Repository Systems (Qian & Bock, 2005), e-commerce (DeLone & McLean, 2004), e-Government systems (Wang & Liao, 2008) and information systems (Iivari, 2005).…”
Section: Delone and Mclean's Iss Modelmentioning
confidence: 99%